Long-term trends in blood pressure and hypertension in Russia: an analysis of data from 14 health surveys conducted in 1975-2017 - Elena Churilova; Vladimir M. Shkolnikov; Svetlana A. Shalnova; Alexander V. Kudryavtsev; Sofia Malyutina; Odd Nilssen; Tiina Laatikainen; David A. Leon (BMC, 2021)
Abstract Background Hypertension is recognized as an important contributor to high cardiovascular mortality in Russia. A comprehensive analysis of data from Russian studies that measured blood pressure in population-based samples has not been previously undertaken. This study aims to identify trends and patterns in mean blood pressure and the prevalence of hypertension in Russia over the most recent 40 years. Methods We obtained anonymized individual records of blood pressure measurements from 14 surveys conducted in Russia in 1975-2017 relating to a total of 137,687 individuals. For comparative purposes we obtained equivalent data from 4 surveys in the USA and England for 23,864 individuals. A meta-regression on aggregated data adjusted for education was undertaken to estimate time trends in mean systolic and diastolic blood pressure, the prevalence of elevated blood pressure (> 140/90 mmHg), and hypertension (defined as elevated blood pressure and/or the use of blood pressure-lowering) medication. A meta-analysis of pooled individual-level data was used to assess male-female differences in blood pressure and hypertension. Results During the period 1975-2017 mean blood pressure, the prevalence of elevated blood pressure and hypertension remained stable among Russian men. Among Russian women, mean systolic blood pressure decreased at an annual rate of 0.25 mmHg (p < 0.1) at age 35-54 years and by 0.8 mmHg (p < 0.01) at ages 55 and over. The prevalence of elevated blood pressure also decreased by 0.8% per year (p < 0.01), but the prevalence of hypertension remained stable. Mean blood pressure and prevalence of hypertension were higher in Russia compared to the USA and England at all ages and for both sexes. Conclusions In contrast to the generally observed downward trend in elevated blood pressure in many other countries, levels in Russia have changed little over the past 40 years, although there are some positive trends among women. Improved strategies to bring down the high levels of mean blood pressure and hypertension in Russia compared to countries such as England and the USA are important to further reduce the high burden of CVD in Russia.